Determinan ketidakpatuhan wajib pajak Pajak penghasilan studi kasus pada wajib pajak orang pribadi yang memiliki usaha atau Yang melakukan pekerjaan bebas yang terdaftar di kpp pratamaSurakarta) - Hidayati, Fitria Nurul; Aris, Msi, Drs. Muhammad Abdul Aris, M.Si (2016)
This study aimed to analyze the determinans of noncompliance taxpayer that the tax system of justice perception, social norms, moral norms, the risk of fraud is detected, the magnitude of the sanctions, religiosity, the intention to behave disobey the attitude of the taxpayer. The population in this study are all taxpayers freelance registered at the KPP Pratama Surakarta. While the sample is an individual taxpayer casual employees listed on KPP Pratama Surakarta. This research uses accidental sampling technique, in order to obtain a sample of 100 individual taxpayers free labor. Theory of Planned Behavior is used to describe the relationship between variables. Data analysis technique used is multiple linear regression. The results of this study indicate that the perception of the justice system of taxation, social norms, moral norms, the risk of fraud is detected, the magnitude of the sanctions, religiosity, the intention to behave disobey, attitude taxpayer noncompliance proved to be a determinant of the taxpayer.